Posterior Circulation Endovascular Thrombectomy for Large-Vessel Occlusion: Predictors of Favorable Clinical Outcome and Analysis of First-Pass Effect - Alexandre, A.M.; Valente, I.; Consoli, A.; Piano, M.; Renieri, L.; Gabrieli, J.D.; Russo, R.; Caragliano, A.A.; Ruggiero, M.; Saletti, A.; Lazzarotti, G.A.; Pileggi, M.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Successful vessel recanalization in posterior circulation large-vessel occlusion is considered crucial, though the evidence of clinical usefulness, compared with the anterior circulation, is not still determined. The aim of this study was to evaluate predictors of favorable clinical outcome and to analyze the effect of first-pass thrombectomy.MATERIALS AND METHODS: A retrospective, multicenter, observational study was conducted in 10 high-volume stroke centers in Europe, including the period from January 2016 to July 2019. Only patients with an acute basilar artery occlusion or a single, dominant vertebral artery occlusion (“functional” basilar artery occlusion) who had a 3-month mRS were included. Clinical, procedural, and radiologic data were evaluated, and the association between these parameters and both the functional outcome and the first-pass effect was assessed.RESULTS: A total of 191 patients were included. A lower baseline NIHSS score (adjusted OR, 0.77; 95% CI, 0.61–0.96; P = .025) and higher baseline MR imaging posterior circulation ASPECTS (adjusted OR, 3.01; 95% CI, 1.03–8.76; P = .043) were predictors of better outcomes. The use of large-bore catheters (adjusted OR, 2.25; 95% CI, 1.08–4.67; P = .030) was a positive predictor of successful reperfusion at first-pass, while the use of a combined technique was a negative predictor (adjusted OR, 0.26; 95% CI, 0.09–0.76; P = .014).CONCLUSIONS: The analysis of our retrospective series demonstrates that a lower baseline NIHSS score and a higher MR imaging posterior circulation ASPECTS were predictors of good clinical outcome. The use of large-bore catheters was a positive predictor of first-pass modified TICI 2b/3; the use of a combined technique was a negative predictor.BAObasilar artery occlusionF-P mTICIfirst-pass effect mTICIIQRinterquartile rangemTICImodified TICIpc-ASPECTSposterior circulation ASPECTSpc-LVOlarge-vessel occlusion of the posterior circulation